Enhancing β-Carotene Production in Escherichia coli by Perturbing Central Carbon Metabolism and Improving the NADPH Supply - Wu, Yuanqing; Yan, Panpan; Li, Yang; Liu, Xuewei; Wang, Zhiwen; Chen, Tao; Zhao, Xueming (Frontiers in Bioengineering and Biotechnology, 2020)
Beta (β)-carotene (C40H56; a provitamin) is a particularly important carotenoid for human health. Many studies have focused on engineering Escherichia coli as an efficient heterologous producer of β-carotene. Moreover, several strains with potential for use in the industrial production of this provitamin have already been constructed via different metabolic engineering strategies. In this study, we aimed to improve the β-carotene-producing capacity of our previously engineered E. coli strain ZF43ΔgdhA through further gene deletion and metabolic pathway manipulations. Deletion of the zwf gene increased the resultant strain's β-carotene production and content by 5.1 and 32.5%, respectively, relative to the values of strain ZF43ΔgdhA, but decreased the biomass by 26.2%. Deletion of the ptsHIcrr operon further increased the β-carotene production titer from 122.0 to 197.4 mg/L, but the provitamin content was decreased. Subsequently, comparative transcriptomic analysis was used to explore the dynamic transcriptional responses of the strains to the blockade of the pentose phosphate pathway and inactivation of the phosphotransferase system. Lastly, based on the analyses of comparative transcriptome and reduction cofactor, several strategies to increase the NADPH supply were evaluated for enhancement of the β-carotene content. The combination of yjgB gene deletion and nadK overexpression led to increased β-carotene production and content. The best strain, ECW4/p5C-nadK, produced 266.4 mg/L of β-carotene in flask culture and 2,579.1 mg/L in a 5-L bioreactor. The latter value is the highest reported from production via the methylerythritol phosphate pathway in E. coli. Although the strategies applied is routine in this study, the combinations reported were first implemented, are simple but efficient and will be helpful for the production of many other natural products, especially isoprenoids. Importantly, we demonstrated that the use of the methylerythritol phosphate pathway alone for efficient β-carotene biosynthesis could be achieved via appropriate modifications of the cell metabolic functions.